Why does narrative need rescuing from qualitative research? - Atkinson, Paul, 1947- ([Thousand Oaks, Calif. : SAGE], 2010)
Professor Atkinson argues that narrative is important in its own right and that enough respect is not usually paid to narrative analysis by qualitative research.
"SAGE research methods online."
Title from home page (viewed Jan. 26, 2011).
Online video.
Includes transcript.
Specialized.
Mode of access: World Wide Web.
Keywords: elektronické knihy; electronic books; Narrative inquiry (Research method) -- Evaluation; Qualitative research